An Electronic Slime-Based Epidermal Electrode Using Carbon Nanocomposites for Biosignal Sensing - Yu Feng; Hui Sun; Meng Chen; Cong Wu; Jiankun Li; Zhi Li; Kremena Makasheva; Na Liu; Guanglie Zhang; Wen Jung Li (IEEE Open Journal of Nanotechnology)
Epidermal sensing electrodes, a key type of advanced wearable device, play a crucial role in biosignal sensing. Recent advancements in functional nanomaterials have propelled the development of these electrodes; however, their fabrication often involves complex processes and expensive raw materials. While significant progress has been made in enhancing the biocompatibility of electrodes through the use of human-friendly materials, improvements in flexibility and conductivity are still needed to ensure optimal skin conformability and compliance. In this study, we present an innovative epidermal sensing electrode constructed from electronic slime (E-slime), which is synthesized through a simple one-step, one-pot method utilizing widely available and cost-effective carbon nanocomposites. The E-slime electrode exhibits exceptional deformability, flexibility, and self-healing properties, ensuring mechanical compliance and effective skin adherence for epidermal applications. Our results demonstrate the electrode's capability in biosignal sensing, including electrocardiogram (ECG) monitoring with a high signal-to-noise ratio (SNR) of 46dB and electromyogram (EMG) monitoring for real-time human-robot interaction. This work introduces a novel strategy for the design and fabrication of epidermal electrodes, offering high conformability, low impedance, and superior signal quality, which holds significant promise for applications in intelligent healthcare monitoring and human-machine interfaces.